Reconstruction of Criminal Liability of State Owned Enterprise Corporations in Procurement Corruption through a Fictitious Subcontracting Scheme - Akbarudin Noor; Bambang Soesatyo (Journal of Legal and Cultural Analytics, 2026)
Corruption in the procurement of goods and services within Indonesian State-Owned Enterprises (SOEs), particularly through fictitious subcontracting schemes, poses serious challenges to transparency, accountability, and state financial management. Existing corporate criminal liability frameworks have not adequately addressed the complex structure of SOEs, especially in attributing responsibility for corruption involving layered contractual arrangements. This study aims to reconstruct the concept of corporate criminal liability of SOEs in such cases using a normative juridical approach with statutory, conceptual, and case analyses. The findings reveal that current regulations focus mainly on individual accountability, allowing corporate entities to avoid effective sanctions due to unclear attribution of intent and responsibility. Therefore, a reconstructed framework is proposed to strengthen institutional accountability alongside individual liability, ensuring greater legal certainty, justice, and more effective anti-corruption enforcement in public procurement.